Roles of fermented plant-, dairy- and meat-based foods in the modulation of allergic responses - Abd Rahim, Muhamad Hafiz; Hazrin-Chong, Nur Hazlin; Harith, Hanis Hazeera; Wan-Mohtar, Wan Abd Al Qadr Imad; Sukor, Rashidah (Tsinghua University Press, 2023)
This review attempts to delineate the effects and roles of fermented foods on allergic responses (AR), specifically from milk, plant, and meat sources. Evidence for AR alleviation and aggravation were noted for many different fermented food groups. Positive outcomes on AR through fermented foods could be linked to microbial hydrolysis of food allergens, improvement in gut microbiota robustness, and modulation of the immune system that promotes a balance between T helper 1 (Th1) and Th2 cells. Studies on plant-based, non-protein rich fermented foods tend to show more favourable results compared to those on meat-based or protein-rich group. The usage of specific and known starter cultures are helpful in alleviating AR, as in the case for many yogurt, Kefir or Dahi products. Sufficient fermentation time was also deemed important, exemplified in studies that showed inefficient AR reduction through consumption of fresh cheese. However, formation of new allergens through fermentation of certain meat-based foods, or by using specific fermenting microbes (e.g. Penicillium sp.), is possible. Thus, combination of starter cultures and food substrates must be considered in preventing or eliminating AR from intake of these foods. This review may aid consumers to make informed decision during the consumption of fermented food.